Expanding carbon capture capacity: uncovering additional CO2 adsorption sites in imine-linked porous organic cages. Issue 17 (30th March 2021) - Li, Zezhong John; Srebnik, Simcha
Abstract : Three types of CO2 adsorption sites are identified for a 15-crown-5 ether-substituted porous organic cage. Each CO2 molecule in the image represents a possible adsorption site, with the numerals corresponding to the site type. Abstract : With an increasing need to develop carbon capture technologies, research regarding the use of cage-based porous materials has garnered great interest. Typically, the study of gas adsorption in porous organic cages (POCs) has focused on the gas uptake inside the cage cavity. By using molecular dynamics simulation, this study reveals the presence of eight sites outside the cavity of a 15-crown-5 ether-substituted imine-linked POC which could enhance carbon dioxide adsorption capacity. Adsorption on these sites is likely stabilized by the functional groups on the cage vertices and the imine groups on the faces of the POC. These external adsorption sites have a higher CO2 adsorption capacity and greater sensitivity to temperature and pressure changes than the sites within the cage cavity. These characteristics are particularly favourable for applications based on pressure- and temperature-swing separation.